PENGARUH NILAI EMOSIONAL, SOSIAL, KUALITAS, DAN FUNGSIONAL TERHADAP SERTIFIKASI ISPO DI KABUPATEN BUNGO (The Influence Of Value Dimension On ISPO Certification In Bungo Regency) - ROCHAENI, SITI; USMANTO, GIVAN MASSA ADRIAN (Universitas Mulawarman (University of Mulawarman), 2025)
This study aims to analyze the influence of the value dimension, namely the emotional, social, quality, and functional values of oil palm farmers on Indonesian Sustainable Palm Oil (ISPO) certification in Bungo Regency. This research focuses on oil palm farmers in smallholder plantations in Bungo Regency that have or have not been ISPO certified, with the background of low ISPO certification even though the government has required certification for every business actor, including farmers. The study used the purposive sampling method with Stuctural Equation Modeling-Partial Least Square (SEM-PLS) analysis. ISPO certification as a bound variable and emotional, social, quality, and functional values as independent variables. The results showed that emotional value and quality value had a significant effect on ISPO certification, while social value and functional value had a significant effect. This indicates that a sense of satisfaction, comfort, and security, as well as short-term benefits such as increased cultivation and long-term incentives for smallholder participation rather than social recognition. Farmers also consider the cost for the certificate to be a burden and a complicated certification process. Plus there is no increase in income after participating in ISPO certification.